Aspek Feminisme dalam Novel Aku Lupa bahwa Aku Perempuan Karya Ihsan Abdul Quddus - Endang Sulistyaniningsih; Fatimah Fatimah; As’ad As’ad (Pujangga: Jurnal Bahasa dan Sastra, 2022)
This study aims to determine the aspect of feminism in the novel Aku Lupa That Aku Perempuan by Ihsan Abdul Quddus. The method used in this study is a qualitative descriptive approach with the research technique used is content analysis. stereotypes, violence, and double burden. In this study, there are 50 aspects of feminism in the novel Aku Lupa That Aku Perempuan by Ihsan Abdul Quddus. The use of aspects of feminism found in the novel, namely there are 6 marginalizations (12%), 13 subordination (26%), 14 stereotypes (28%), 5 violence (10%), 12 double burdens (24%). Based on the description above, it can be seen that the dominant form of gender inequality in Ihsan Abdul Quddus' novel Aku Lupa That Aku Perempuan is stereotyped as many as 14 quotes in a sentence.